2018
DOI: 10.18295/squmj.2018.18.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of an Aspergillus fumigatus-Specific Immunoglobulin G Reference Range in an Adult Omani Population

Abstract: The specific IgG reference range within a healthy adult Omani population was comparable to those reported in other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 15 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Moreover, many previous studies confirmed A. fumigatus as the main causal pathogen (Page et al, 2016(Page et al, , 2018Al-Rahman et al, 2018;Sehgal et al, 2018;Lee et al, 2020). A previous study found that A. niger was the most frequently isolated Aspergillus spp.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Moreover, many previous studies confirmed A. fumigatus as the main causal pathogen (Page et al, 2016(Page et al, , 2018Al-Rahman et al, 2018;Sehgal et al, 2018;Lee et al, 2020). A previous study found that A. niger was the most frequently isolated Aspergillus spp.…”
Section: Discussionmentioning
confidence: 84%
“…exists in a wide range of environments. A substantial number of species are pathogens that are responsible for a collective group of clinical diseases referred to as aspergillosis ( Al-Rahman et al, 2018 ). Among them, Aspergillus fumigatus is the main cause of disease, accounting for approximately 80% of aspergillosis ( Al-Rahman et al, 2018 ; Jat et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations